2020
DOI: 10.1186/s41235-020-00250-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in strategy use and performance during fault diagnosis

Abstract: Background Research on causal reasoning often uses group-level data analyses that downplay individual differences and simple reasoning problems that are unrepresentative of everyday reasoning. In three empirical studies, we used an individual differences approach to investigate the cognitive processes people used in fault diagnosis, which is a complex diagnostic reasoning task. After first showing how high-level fault diagnosis strategies can be composed of simpler causal inferences, we discussed how two of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 75 publications
2
16
0
Order By: Relevance
“…In line with the general finding that apt troubleshooters make fewer tests but take longer for each of them, while poor troubleshooters conduct more tests with shorter time intervals between them (Morris & Rouse, 1985;Rouse & Rouse, 1979;Shreeves et al, 2020), Gugerty (2007) found a strong negative correlation between the…”
Section: Visual Aids For Solving Ntpssupporting
confidence: 81%
See 4 more Smart Citations
“…In line with the general finding that apt troubleshooters make fewer tests but take longer for each of them, while poor troubleshooters conduct more tests with shorter time intervals between them (Morris & Rouse, 1985;Rouse & Rouse, 1979;Shreeves et al, 2020), Gugerty (2007) found a strong negative correlation between the…”
Section: Visual Aids For Solving Ntpssupporting
confidence: 81%
“…Missing information about a system, like the number and location of faulty elements, increases uncertainty. Causal reasoning, including iterations of hypothesis generation and testing, narrows the problem space and reduces uncertainty throughout the processes of fault diagnosis and problem solving (Shreeves, Gugerty, & Moore, 2020). Usually, the operators available for diagnosing or removing the fault are routine procedures that need to be known and practiced, while for new problems they are often indeterminate (Jonassen & Hung, 2006; Morrison & Duncan, 1988).…”
Section: The Complexity Of Troubleshooting Problemsmentioning
confidence: 99%
See 3 more Smart Citations